Electrospun Magnetic Porous Membranes for Bone Tissue Engineering - Marinho, Hélder Azevedo (2023)
Organ transplantation has been and still is the classic method to heal patients with any kind of organ disease. However, this approach has several downsides, such as donor scarcity, short preservation time of the organs, high cost, and post-operation complications. Tissue engineering, a domain that aims to develop adequate substitutes that restore, maintain, and improve tissue functions, is a relatively new alternative in the regenerative medicine field that overcomes organ transplantation issues. In this work, new membranes for bone tissue engineering were produced from electrospun PLA membranes with poly(ionic liquid) and superparamagnetic iron oxide nanoparticles (SPIONs). The membranes were submitted to supercritical drying with CO2, to induce porosity for better cell attachment, a procedure that also enhanced the crystallinity of the membranes. The samples were characterized by ATR-FTIR, TGA, XRD, SEM and magnetic hyperthermia. The results showed that all the samples with nanoparticles are suited for local cancer treatment, as it is possible to reach the temperature to eliminate tumoral cells by magnetic hyperthermia treatment. The samples were evaluated for cytotoxicity according to ISO 10993-5 with a human osteosarcoma cell line and the lowest registered value for cell viability was 94%, meaning that no sample presented cytotoxicity.